A Low-Profile Dual-Band Filtering Hybrid Antenna With Broadside Radiation Based on Patch and SIW Resonators - Qianwen Liu (IEEE, 2021)
This paper presents a differentially fed dual-band hybrid antenna with broadside radiation, enhanced bandwidth, and high selectivity. The proposed antenna is constructed using a single- layer substrate based on rectangular patch resonator and substrate integrated waveguide (SIW) cavity. Herein, TM10 and TM12 modes of the rectangular patch resonator, together with TE21 and TE23 modes of the rectangular SIW cavity, are selected for resonances in the concerned dual-band radiation. Among them, TM10 and TE21 are employed for the lower passband, while TM12 and TE23 for the higher passband. Besides, for achieving broadside radiation performances in both bands, two arrays of shorting pins are loaded in the rectangular patch resonator and the constituted electric wall surround the rectangular SIW cavity is properly truncated to reshape the radiation patterns of TM12 and TE23, respectively. Notably, the resonant and radiation properties of all the involved modes are obtained with theoretical deduction. Furthermore, the cascaded trisection composed of the SIW cavity, the patch resonator, and the radiation impedance creates two radiation nulls in each upper stopband of both passbands and the mixed coupling between two resonators generates another radiation null to be located in the lower stopband of the higher passband. For demonstration, a prototype antenna with the dual bands at 3.5 and 5.8 GHz is fabricated and tested. The measured results show that the antenna has achieved an improved bandwidth ( $|S_{ dd11}| < -10$ dB) from 3.26 to 3.58 GHz and 5.60 to 5.90 GHz, respectively, with stable broadside gains of around 8.5 dBi. In addition, in the stopband, three radiation nulls are created at 3.71, 5.32, and 6.12 GHz for effective enhancement of dual-band frequency selectivity.